2022
DOI: 10.6026/97320630018645
|View full text |Cite
|
Sign up to set email alerts
|

Anti-inflammatory and cytotoxic effect of lycopene and raspberry in-situ gel

Abstract: Preparation of an in-situ gel containing lycopene and raspberry plant formulation and analysis of its anti-inflammatory and antioxidant effects is described. Lycopene is known for its anticancer and antioxidant activity. It induces apoptosis, thereby reducing the cancer cells, and also reduces the injury of cells due to oxidative activity. Similarly, raspberry also contains antioxidants properties which can help to reduce oxidative stress and chronic inflammation. This study includes extracts containing 25% of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 37 publications
(38 reference statements)
0
0
0
Order By: Relevance
“…In a study done by Chaithanya VM et al, the gel prepared using lycopene and Raspberry plant extract showed significant anti-inflammatory activity on BSA protein [ 28 ]. In another study, the nano-herbal formulation prepared using raspberry, lycopene, green tea, and silver nanoparticles showed strong anti-inflammatory activity on BSA protein [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a study done by Chaithanya VM et al, the gel prepared using lycopene and Raspberry plant extract showed significant anti-inflammatory activity on BSA protein [ 28 ]. In another study, the nano-herbal formulation prepared using raspberry, lycopene, green tea, and silver nanoparticles showed strong anti-inflammatory activity on BSA protein [ 29 ].…”
Section: Discussionmentioning
confidence: 99%